A Founder Pathogenic Variant of PPIB Unique to Chinese Population Causes Osteogenesis Imperfecta IX - Zhu, Wenting; Yan, Kai; Chen, Xijing; Zhao, Wei; Wu, Yiqing; Tang, Huanna; Chen, Ming; Wu, Jian; Wang, Pengpeng; Zhang, Runju; Shen, Yiping; Zhang, Dan (Frontiers in Genetics, 2021)
Background: Osteogenesis imperfecta (OI) is a heterogeneous genetic disorder characterized by bone fragility. PPIB pathogenic variants cause a perinatal lethal form of OI type IX. A limited number of pathogenic variants had been reported so far worldwide. Methods: We identified a rare pedigree whose phenotype was highly consistent with OI-IX. Exome sequencing was performed to uncover the causal variants. The variant pathogenicity was classified following the ACMG/AMP guidelines. The founder effect and the age of the variant were assessed. Results: We identified a homozygous missense variant c.509G>A/p.G170D in PPIB in an affected fetus. This variant is a Chinese specific allele and can now be classified as pathogenic. We estimated the allele frequency (AF) of this variant to be 0.0000427 in a Chinese cohort involving 128,781 individuals. All patients and carriers shared a common haplotype, indicative of a founder effect. The estimated age of variant was 65160 years. We further identified pathogenic variants of PPIB in gnomAD and ClinVar databases, the conserved estimation of OI type IX incidence to be 1/1,000,000 in Chinese population. Conclusion: We reported a founder pathogenic variant in PPIB specific to Chinese population. We further provided our initial estimation of OI-IX disease incidence in China.